Preparation and characterization of eco-friendly hybrid biocomposites from natural rubber, biocarbon, and carbon black - D. M. Paleri; A. Rodriguez-Uribe; M. Misra; A. K. Mohanty (eXPRESS Polymer Letters)
This study aims to investigate the effect of different carbonaceous fillers, carbon black (CB) biocarbon (BC), and a hybrid filler of both (BC-CB), in a natural rubber matrix. It was found that the addition of hybrid filler based on a sustainable biocarbon (BC) and carbon black (CB) revealed a significant effect on reducing the rolling resistance properties. Dried distillers’ grain with solubles (DDGS), a co-product from corn ethanol industry pyrolyzed at 900 °C, was used to produce the biocarbon. As compared to the carbon black, the particle size of the biocarbon was larger which was reflected in the tensile strength of the biocarbon composites. This observation was correlated using swelling studies and found to be proportional to their crosslink density. The thermal characterizations showed similar transitions and degradation mechanisms in all the composites, which confirmed a comparatively similar behavior of BC with CB. Moreover, these findings justify further tuning of biocarbon into nanosize and this could expand the scope in the utilization of this sustainable filler for the fabrication of various rubber products such as tires and hoses, etc.